Distribution of antigens of the HLA-system in married couples with reproductive disorders - A. N. Kiseleva; E. V. Butina; N. V. Isaeva; G. A. Zaitseva; N. M. Pozdeev; V. V. Ovchinnikov (Акушерство, гинекология и репродукция, 2019)
Aim: to study the distribution of HLA-antigens in married couples with failed conception and/or carrying of pregnancy, and to assess the occurrence rate and the presence of common alleles of the main histocompatibility complex in couples with infertility and miscarriages.Materials and methods. We conducted HLA-typing of 198 married couples with aggravated obstetric history. The main inclusion criteria were conception failures and unsuccessful outcomes of previous pregnancies. The HLA-class I antigen typing was carried out using a standard micro-lymphocyte-toxic test («Gisans», Russia); for the class II HLA-antigens, real-time polymerase chain reaction («DNA-Technology», Russia) was used. Based on the obstetric and gynecological history, the patients were divided into 2 subgroups: 1st – those with infertility and 2nd– with recurrent miscarriages. The comparison group included 101 married couples with no aggravated obstetric history, no infectious, no endocrine or anatomical abnormalities, and having 2 or more children. The occurrence rates of classes I and II HLA-antigens in women and men from the examined groups were compared with those in healthy individuals living in the same area.Results. In the examined couples with recurrent miscarriages, the HLA-A11 antigen occurred significantly more often in men, and HLA-В35 antigen – less often in women. In women of the infertile couples, HLA-A19 antigen was detected more often than in couples with children. In women with infertility, the HLA-DRB1*08 and HLA-DQA1*0401 alleles were less common than in women without fertility disorders. In the examined couples with infertility and recurrent miscarriages, statistically significant predominance of 3 genes common to the HLA class II system was found. In couples with normal fertility functions, the absence of homologous alleles of the HLA class II system in their genotypes was typical.Conclusion. HLA typing allows for predicting the risk of infertility and reproductive failure.